Tracking the Fortunes of Corporate Psychedelia - Sandy Brian Hager (City Political Economy Research Centre, 2024)
In recent years, new biotech companies have emerged hoping to cash in on a medical psychedelics market expected to be worth billions. This article examines the business models of two of the largest such companies. According to conventional wisdom, for-profit players are best positioned to deliver new cures for mental illness at scale because of their ability to tap capital markets. The analysis presented here challenges this story on two counts. First, it argues that profitability in the pharmaceutical business depends not on rapid scaling per se, but on controlling and restricting access to maintain pricing power. Second, it claims that the unruliness of sychedelics – manifested in the presence of cheap generics, murky intellectual property claims, and high costs of administration – raises serious questions about their commercial viability. The article then assesses the sector's embrace of Johnson and Johnson's patented form of esketamine, Spravato, as its prototype for commercialization. Spravato may provide a pathway for profitability, but patients must contend with high prices and a drug that provides only short-term relief and requires indefinite dosing. Rather than disrupt Big Pharma, corporate psychedelia replicates its main features, raising questions about its claims to tackle the mental health crisis.
Keywords: P1; I1; I11; 330; psychedelics; pharmaceutical; medicalization; mental health crisis; business models